Accountings Students Following Test Certification Accounting Yunior Test In Indonesia - Vina Arnita; Heriyati Chrisna (Economics, Business and Management Science Journal, 2022)
This study aims to prove the factors (economic motivation, career motivation, self-competence, degree motivation) that affect accounting students taking the certification test accounting junior in the accounting study program at the Panca Budi Development University, Medan. Type The data in this research process uses primary data where the data is obtained from several respondents virtually by using a questionnaire in the form of Google Forms (GForms). The population used in this study were all students of the study program accounting for the University of Development Panca Budi Medan with a 2017-2019 stamp of 1,564 student. The sample used was 150 students by using the Purposive Sampling. The test results in this study show: (1) economic motivation significant effect on accounting students taking the accounting junior certification test. (2) career motivation has no significant effect on students taking the junior certification test accountancy. (3) self-competence motivation has no effect on students taking the test accounting junior certification. (4) degree motivation has a significant effect on students following accounting junior certification test.